(untitled) (Indian Journal of Public Health Research & Development, 2021)
Vitamin D deficiency is common in northern India but there are limited data in pregnant women and neonates. This study aimed to determine the prevalence of vitamin D levels in cord blood of newborns and the association with maternal vitamin D. A total of 50 pregnant women and their neonates were included. Clinical data and venous maternal blood for calcium,phosphate, albumin, alkaline phosphatase, magnesium, intact parathyroid hormone, and vitamin D were obtained on the day of labor. Cord blood was collected following delivery to evaluate vitamin D status of newborns. Mean serum maternal and cord blood 25OHD levels were 25.42 ± 8.07 and 14.85 ± 5.13 ng/mL. The prevalence of vitamin D deficiency (25OHD < 12 ng/ mL) and insufficiency (25OHD 12–20ng/mL) in cord blood of newborns were 20.2 and 69.1%,respectively. There was a significant correlation between maternal and cord blood vitamin D levels (P< 0.001). The factors associated with cord blood vitamin D deficiency were low maternal 25OHD level and no vitamin D supplement during pregnancy. Conclusion: There is a high prevalence of vitamin D deficiency among the neonates. Adequate prenatal vitamin D supplementation should be implemented as routine antenatal care.